2021
DOI: 10.1186/s12947-021-00256-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of prenatal changes in fetal cardiac morphology and function in maternal diabetes mellitus using a novel fetal speckle-tracking analysis: a prospective cohort study

Abstract: Background Due to metabolic changes in the second trimester and the increasing number of pregnant women with obesity and advanced maternal age, the incidence of gestational diabetes mellitus (GDM) remains high. This study aimed to evaluate the effects of GDM on fetal cardiac morphology and function, and to determine whether these changes increase with increasing estimated fetal weight (EFW). Methods Fifty-eight women with GDM (GDM group) and 58 wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 29 publications
4
19
2
Order By: Relevance
“…The cardiac shape is a good indicator of cardiac function [ 25 ]. Some studies reported rounder hearts in GD fetuses [ 20 , 21 , 22 ], but novel studies using FetalHQ ® to compare GD to healthy fetuses did not find a significant difference in GSI [ 8 , 9 ], which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The cardiac shape is a good indicator of cardiac function [ 25 ]. Some studies reported rounder hearts in GD fetuses [ 20 , 21 , 22 ], but novel studies using FetalHQ ® to compare GD to healthy fetuses did not find a significant difference in GSI [ 8 , 9 ], which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Strain is another sensitive marker of cardiac function. Longitudinal strain is used more often than radial or circumferential strain to evaluate myocardial deformation [ 21 ]. There are conflicting results regarding fetal cardiac strain in maternal diabetes, which could be explained by the different study design (most studies did not differentiate pregestational diabetes of GD effects, while some studies used the older GD diagnosis criteria).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 In our study, the growing trend of right ventricular end-diastolic diameter (RV) in the GDM group became higher than that in the control group, and the difference in two groups became larger in the whole observation period. The rapid increase of RV in GDM group may affect the entire cardiac structure of the fetal myocardium and increase the spherical index, [18][19][20] which may be a sign of reduced myocardial compliance.…”
Section: Discussionmentioning
confidence: 99%
“…It can analyze the morphological and functional changes of each segment from the base of the ventricle to the apex in a more detailed and accurate manner; FAC and GLS of the left and right ventricles can also be obtained. Previous studies have demonstrated (21)(22)(23) that these indicators can accurately assess the systolic function of the left and right ventricles. The results of this study showed that fetal GSI, FAC, and GLS were not correlated with fetal GA.…”
Section: Discussionmentioning
confidence: 99%